Eye-tracking as a method for legal research - Christoph Engel; Rima-Maria Rahal (Max Planck Institute for Research on Collective Goods, 2022)
Legal research is a repeat offender - in the best sense of the term - when it comes to making use of empirical and experimental methods borrowed from other disciplines. We anticipate that the field's response to developments in eye-tracking research will be no different. Our aim is to aid legal researchers in the uptake of eye-tracking as a method to address questions related to cognitive processes involved in matters of law abidance, legal intervention, and the generation of new legal rules. We discuss methodological challenges of empiri-cally studying thinking and reasoning as the mechanisms underlying behavior, and introduce eye-tracking as our method of choice for obtaining high-resolution traces of visual attention. We delineate advantages and challenges of this methodological approach, and outline which concepts legal researchers can hope to measure with a toy example. We conclude by outlining some of the various research avenues in legal research for which we predict a benefit from adopting eye-tracking to their methodological toolbox.
hdl:21.11116/0000-000B-5C1D-F
Keywords: 330; methods; eye-tracking; cognition; process tracing